Isolamento e seleção de bactérias lipolíticas - Souza, Camila Michele Pereira de (Universidade Federal Rural do Semi-Árido, 2016)
The production of enzymes by microorganisms is advantageous that the vegetable and animal origin due to the ease in obtaining and handling them. The processes catalyzed by microbial enzymes are generally faster, more efficient, less costly and environmentally sustainable than those that are made with chemical catalysts. This fact directly influences the increased use of these enzymes in industrial environment. Lipases are enzymes that catalyze the hydrolysis of long chain triglyceride transforming them into glycerides and fatty acids. Microbial lipases are part of one of the most important groups of enzymes for industrial application. Besides being involved in certain processes in the food, pharmaceutical, cosmetics, textile, paper and leather, these enzymes are also used in supplementation of animal feed that have deficiency in processing lipids. On the promising potential of these enzymes, this work had as main objective the isolation of bacteria producing lipase from samples from hot springs with temperatures ranging from 37-54 ° C. The most promising lines for lipase production were selected by testing the Rhodamine B and p-nitrophenyl palmitate (pNPP). Of the 51 isolated bacterial strains, 17 demonstrated the potential lipolytic Rhodamine test. Of these, nine were selected in the enzyme activity test (pNPP) verifying that the cultivation temperature influences the production of enzymes. The temperature of 30 ° C was the most favorable to growth and production of the enzymes. For the enzymatic activity temperature, it was found that one of the lines has greater activity at 70 ° C, thereby increasing interest in the use of same in the industrial environment the thermostable enzyme production. The results reflect the importance of studying the biotechnological potential of the microbiota associated with thermal environments for prospecting producing strains of lipases, and future agro-industrial applications
Isolation and selection of lipolytic bacteria
Keywords: Enzima; Lipase; Microrganismos; Bactéria; Enzyme; Lipase; Microorganisms; Bacteria; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL